Alien flora in Calabria (Southern Italy): an updated checklist - Spampinato, Giovanni (2022)
An updated checklist of the Calabrian alien vascular flora is presented. By way of field, bibliographic, and herbarium research, we recorded 382 alien taxa (representing almost 14% of all regional flora), of which 371 are angiosperms, nine gymnosperms, and two ferns. In relation to the state of spread, the majority of alien species are casual (207 taxa; 54%), followed by naturalized (127; 33%) and invasive (48; 13%), these last include four on the list of Union Concern, sensu Regulation (EU) no. 1143/2014. The most represented families are Asteraceae (39 taxa) and Poaceae (39). Among genera, Amaranthus (nine taxa), Prunus, Euphorbia, and Oxalis (seven taxa) make up those with the greatest number of taxa. A total of 21 taxa were reported for the first time, three of them are new to the European flora (Camptosema rubicundum, Musa xparadisiaca and, only for continental Europe, Ipomoea hederacea), two to the Italian peninsula (Pelargonium graveolens, Schinus terebinthifolia) and 16 to the Calabrian flora (Aeonium arboreum, Asparagus asparagoides, Aspidistra elatior, Bidens sulphurea, Catalpa bignonioides, Citrus xaurantium, Crassula ovata, Cucurbita ficifolia, Dimorphotheca ecklonis, Graptopetalum paraguayense subsp. paraguayense, Kalanchoe laxiflora, Nicotiana tabacum, Phytolacca dioica, Portulaca umbraticola, Talinum paniculatum, Tecomaria capensis). In terms of residence status, there are 291 neophytes (76%), 73 archaeophytes (19%), and 18 regional aliens (5%); neophytes are the most represented group (45 out of 48) among invasive taxa. Concerning life forms, the two most abundant groups are therophytes (30.1%, 115 taxa) and phanerophytes (29.6%, 113 taxa). Regarding habitats, 72% of alien taxa occur in artificial (199 taxa, 52%) and agricultural habitats (75 taxa, 20%). The majority of alien taxa are native to the Americas (159; 41.6%), numerous aliens also originated in Asia (76; 19.9%) and Africa (56; 14.7%). The majority of taxa were introduced for ornamental purposes (55%). Over the past decade, alien taxa in the flora in Calabria have increased from 190 to the current 382 taxa. While this trend could be linked to some extent to increasing awareness of the problem of alien species and the increasing intensity of research over recent decades, it is also most probably due to new introductions resulting from the globalization that relentlessly affects the whole planet.